2014
DOI: 10.1097/bpo.0000000000000113
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Review of Femoral Nerve Block for Postoperative Analgesia After Knee Surgery in the Pediatric Population

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…Two studies that support the efficacy of FNB demonstrate lower VAS scores, less morphine use, less vomiting, and lower postoperative admission rates in pediatric patients after ACL reconstruction. 32,36 Major complications resulting from FNB are rare. 37 However, cases of motor weakness and transient femoral neuropathy have been reported in the literature.…”
Section: -In-5mentioning
confidence: 99%
“…Two studies that support the efficacy of FNB demonstrate lower VAS scores, less morphine use, less vomiting, and lower postoperative admission rates in pediatric patients after ACL reconstruction. 32,36 Major complications resulting from FNB are rare. 37 However, cases of motor weakness and transient femoral neuropathy have been reported in the literature.…”
Section: -In-5mentioning
confidence: 99%
“…We have previously published our data demonstrating a reduction in hospital admission rate after implementation of our PNC program, reducing the hospital admission rate for knee surgery from 95% in 2010 to 2.5% in 2013 13. In the current study, 91 (77.1%) patients were discharged to home on the day of surgery; that is, comparable to the results of Visoiu et al5 with a 76.7% same day of surgery discharge rate, but higher than the same day discharge rate reported by other groups, including 50% by Ganesh et al,2 35.6% by Gurnaney et al,4 and 4.2% by Ludot et al14 As a result of our high success rate with discharge to home with the PNCs, many of these procedures are now occurring at our outpatient surgery center.…”
Section: Discussionmentioning
confidence: 92%
“…Although this potential limitation is evident in hindsight, at the time this study was designed, we had observed significant postoperative pain associated with the same procedures, as previously reported by our group. 7 The mechanism of action by which dexamethasone prolongs analgesia after peripheral nerve blockade remains to be elucidated. Proposed pharmacodynamics include dexamethasone-induced perineural vasoconstriction slowing the local anesthetic absorption, glucocorticoid receptor activation of inhibitory potassium channels on C-fibers, and systemic anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…At our institution, we have previously described significant postoperative pain associated with knee arthroscopy, such that 61% of patients who underwent knee surgery with FNB required postoperative intravenous opioids, and 3% of patients receiving FNB and undergoing knee arthroscopy without anterior cruciate ligament (ACL) reconstruction required readmission. 7 In our previous experience with these procedures, caregivers reported on follow-up phone calls that patients generally consumed opioid medication every 4 hours after discharge, suggesting the persistence of uncontrolled pain.…”
mentioning
confidence: 99%